3D Micro‐Printing Goes Macro: Tailor‐made materials enable pioneering developments and applications. Issue 5 (7th November 2017) - Rodríguez, Sofía; Frölich, Andreas
Abstract: In 1997, Satoshi Kawata and his colleagues from the Osaka University in Japan introduced a revolutionary method for three‐dimensional microfabrication based on two‐photon polymerization (2PP) [1]. Today, this 3D direct laser writing technique allows for building nano‐, micro‐ and millimeter‐sized objects of almost any desired shape with easy processes along a classical 3D printing workflow. 2PP uses photopolymerizable resins as printable matter. For this purpose, tailor‐made 2PP resins have been designed. They target needs ranging from nanometer resolution printing to reduced aberration patterning and smooth surface finishes. However, when deciding on mesoscale fabrication, the right choice of 3D printing technique is not evident. A novel, tailor‐made resin provides a viable approach for rapid 3D printing on the mesoscale.